Upaya Perbaikan untuk Mengatasi Kesalahan Inspeksi oleh Selector pada Departemen EBM PT. X Menggunakan Metode DMAIC - Gabriella Axelina Limantara; Prayonne Adi (Jurnal Titra, 2021)
X Company is a private multinational company which manufactures a broad range of packaging for makeup and skincare. Quality of the manufactured products is the focus of production process that taken place on X Company, so that the quality inspection are conducted twice. In practice, there is a fairly high number of inspection error done by the inspector. Inspection errors cause a high risk of defective products getting into the hands of customers. Therefore, it is necessary to measure the inspector’s accuracy when conducting inspections using the Attribute Agreement method. Based on the measurement results, it is known that as many as 66.67% of inspectors in the EBM (Extrusion Blow Molding) area have an accuracy level that is below the company given standard. A root cause analysis was carried out to determine the root cause of the problem using the help of fishbone diagram. The root cause are dominated by the aspects of man and method. The results of the analysis will be used as a reference in improvement proposals, using the help of the design thinking method.